The Possibility of Developing English Magic Tricks Problem-Based Activities to Enhance Senior High School Students’ Engagement - Ikhsanudin Ikhsanudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
One of the critical factors of successful teaching is the students’ engagement. This research is aimed at producing a set of classroom activities that were designed based on magic tricks problems to engage Indonesian senior high school students in English classes. Such a set of classroom activities wereexpected to be to significantly help teachers implement English language 2013 curriculum in various school situations. As required by the curriculum, Indonesian teachers should promote higher order thinking as an integral part of preparing Indonesian younger generation to be able to compete and to collaborate with human resources across the globe. Through opportunity analysis, design, and development steps, this research has revealed the followings. First, it was necessary to develop English magic trick problem-based activities (EMPA) to enhance senior high school students’ engagement. Second, the architecture of the activities was easy to understand. Last, the problem and language contents were found inline with the curriculum that was being used by all senior high school nationwide. Before publishing them widely, a least one research is necessary to try-out EMPA in “real classrooms.” It is also important to note that the teacher that would use EMPA should understand the concept of problem-based learning and should learn the tricks beforehand.